Valve-Sparing Aortic Root Replacement in a Patient With an FLNA Variant. Issue 6 (November 2022) - Lobbestael, Adam J.; Bupp, Caleb P.; Haw, Marcus P.
We report a case of a 38-year-old female with an FLNA variant who underwent valve-sparing aortic root replacement. FLNA encodes Filamin A, an actin-binding protein. Our patient had aortic root dilation due to this variant. Aortic root repair was conducted using the David procedure, with modifications to account for tissue fragility associated with this genetic condition. This case demonstrates the value of patient-specific genetic information for the timing of surgery and operative course planning.